Analysis of graphic humor in Mundo Gráfico magazine during the Second Spanish Republic (1931-1936) - Nebreda Martín, Lara (Revista General de Información y Documentación, 2025)
The aim of this paper is to examine the humorous drawings published in Mundo Gráfico magazine during the Second Spanish Republic (April 1931 – July 1936). The cartoons featured in this weekly publication are analyzed based on their origin (the original medium in which they were published), authorship, dates, sections in which they appeared, and themes. The findings of this research offer the quantification and analysis of the drawings, and valuable insights into international magazines of the time, Spanish graphic artists, sociocultural aspects, and Mundo Gráfico itself.